Comparative pharmacokinetic interaction profiles of pravastatin, simvastatin, and atorvastatin when coadministered with cytochrome P450 inhibitors - Jacobson, Terry A. (The American journal of cardiology, 2004)
Three-hydroxy-3-methylglutaryl coenzyme-A reductase inhibitors (statins) are first-line treatments for hypercholesterolemia. Although exceedingly well tolerated, treatment with statins incurs a small risk of myopathy or potentially fatal rhabdomyolysis, particularly when coadministered with medications that increase their systemic exposure. Studies compared the multiple-dose pharmacokinetic interaction profiles of pravastatin, simvastatin, and atorvastatin when coadministered with 4 inhibitors of cytochrome P450-3A4 isoenzymes in healthy subjects. Compared with pravastatin alone, coadministration of verapamil, mibefradil, or itraconazole with pravastatin was associated with no significant changes in pravastatin pharmacokinetics. However, concomitant verapamil increased the simvastatin area under the concentration:time curve (AUC) approximately fourfold, the maximum serum concentration (C max) fivefold, and the active metabolite simvastatin acid AUC and C max approximately four- and threefold, respectively (all comparisons p <0.001). Similar (greater than fourfold) important increases in these parameters and a >60% increase in the serum half-life (p = 0.03) of atorvastatin were observed when coadministered with mibefradil. The half-life of atorvastatin also increased by ≈60% (p = 0.052) when coadministered with itraconazole, which elicited a 2.4-fold increase in the C max of atorvastatin and a 47% increase in the AUC (p <0.001 for C max and AUC). Clarithromycin significantly (p <0.001) increased the AUC (and C max) of all 3 statins, most markedly simvastatin (∼10-fold increase in AUC) and simvastatin acid (12-fold), followed by atorvastatin (greater than fourfold) and then pravastatin (almost twofold). Pravastatin has a neutral drug interaction profile relative to cytochrome P450-3A4 inhibitors, but these substrates markedly increase systemic exposure to simvastatin and atorvastatin.